Feeding and breeding management practices for goats in Sabarkantha district of North Gujarat - Warle, R H; Chauhan, H D; Srivastava, A K; Parmar, F V; Pawar, M (Indian Journal of Animal Production and Management, 2018)
A field study was conducted in Sabarkantha district to study the feeding and breeding management practices followed by the Goat owners. Data was collected from two selected talukas from 120 goat owners through personal interview with the help of pre-tested structured interview schedule. The study revealed that majority of respondents (50.83%) allowed their animals for 7 hrs grazing. Majority of goat owners (95.0%) followed stall feeding + grazing, while very few (5%) adopted only stall feeding. Majority of goat owners (91.67%) had availability of green fodder while very few goat owners (12.5%) had availability of dry fodder. It was found that very few respondents (4.17%) fed concentrate to their goats. It was observed that only a meager proportion of respondents (9.17%) provided mineral supplements to their goats. Almost all the respondents (99.17%) have adopted colostrum feeding to kids through suckling. It was revealed that around 60% respondents were detecting the heat by observing bleating + mucous discharge. About 52.50% respondent informed that they utilize their own bucks for breeding. A large number of respondent (61.67%) were taking care during kidding by providing separate space for kidding. Majority of respondents (74.17%) were reported to protect their goats from inclement weather. It may be concluded that feeding and breeding management practices adopted by the goat farmers in the study area were less satisfactory and need more efforts of extension agencies for increasing their level of knowledge